An oesophageal fistula associated with cervical osteomyelitis in a 17‐month‐old Holstein heifer. Issue 1 (26th November 2021) - Guarnieri, Eloi; Berman, Julie; Babkine, Marie
Abstract: A 17‐month‐old Holstein heifer was presented to the Centre Hospitalier Universitaire Vétérinaire in Saint‐Hyacinthe (QC, Canada) for abnormal regurgitation. Upon admission, pain was elicited upon mobilisation of the neck and a left‐sided, painless, fluctuating subcutaneous mass was detected in the area of the fifth and sixth cervical vertebrae. An oesophageal fistula with osteomyelitis of the corresponding vertebrae was diagnosed by medical imaging (endoscopy, ultrasound and radiography) and treated medically. No sequelae were reported in the long term. Considering the low prevalence of abnormal regurgitation in cattle, this paper provides the practitioner with an example of a diagnostic approach.